Benzo[1, 2‐b:4, 5‐b′]dithiophene‐alt‐terthiophene Copolymers Containing Styryl‐Triphenylamine Side Chains: Synthesis and Photovoltaic Performance Optimization with Fullerene Acceptors. Issue 10 (16th April 2013) - Wang, Xitian; Zhang, Zhi‐Guo; Tang, Wenli; Shen, Suling; Liu, Guo; Chi, Dan; Li, Yongfang; Wang, Jizheng
Abstract A new two‐dimensional‐conjugated polymer (PBDTT3‐TPA) containing benzodithiophene (BDT) and a side chain isolation comonomer is designed and synthesized. Interestingly, PBDTT3‐TPA is compatible with higher lowest unoccupied molecular level (LUMO) acceptors of indene‐C60 bisadduct (ICBA), and polymer solar cells based on PBDTT3‐TPA/ICBA show an open‐circuit voltage (VOC) of ca. 0.80 V and a power conversion efficiency of 2.48% under AM1.5G illumination of at 100 mW cm−2. Furthermore, the energy loss in the corresponding fullerene acceptor devices is discussed, and the increase in the observed VOC is explained quantitatively by the up‐shifted LUMO energy of ICBA (0.17 eV) and the reduced saturation current (JSO) in the blends.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>